2022
DOI: 10.1155/2022/5665921
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Tedlar Bags on the Composition of Exhaled Human Breath Samples

Abstract: The PVF Tedlar is widely used for gas collection in clinical diagnostics and environmental research. However, sample collection is frequently associated with the degradation, adsorption, or transformation of sensitive chemicals. Here, we explore to what extent the Tedlar bag collection effects the composition of expired breath samples. Collected breath samples were analyzed using the EESI-MS technique after the storage time of 30 min, 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively. Our results demonstrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Used plastic may be soiled by organic matter from their use, thereby creating a biohazard. Te microbes that grow there, as well as the organic matter, add to the load of greenhouse gases when these bags are heated; however, heating them may also sterilise the material, making it safe for future use, for example, for sealing grain to minimise losses after harvesting [17], for use as hospital gift bags for new mothers [18], or as Tedlar bags for gas storage [19]. Treatments like colouring and plasticisers add another level of uncertainty to the process.…”
Section: Discussionmentioning
confidence: 99%
“…Used plastic may be soiled by organic matter from their use, thereby creating a biohazard. Te microbes that grow there, as well as the organic matter, add to the load of greenhouse gases when these bags are heated; however, heating them may also sterilise the material, making it safe for future use, for example, for sealing grain to minimise losses after harvesting [17], for use as hospital gift bags for new mothers [18], or as Tedlar bags for gas storage [19]. Treatments like colouring and plasticisers add another level of uncertainty to the process.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%